Association between ischaemic stroke aetiology and leptomeningeal collateral status: a retrospective cohort study (Swiss Medical Weekly, 2024)
INTRODUCTION: There is limited understanding of the pathomechanistic relationship between leptomeningeal collateral formation and ischaemic stroke aetiology. We aimed to assess the association of leptomeningeal collateral status and ischaemic stroke aetiology, using the widely recognised “Trial of Org 10172 in Acute Stroke Treatment” (TOAST) classification categorising strokes into five distinct aetiologies.METHODS: Retrospective study of consecutively admitted adult ischaemic stroke patients at a Swiss stroke centre. Leptomeningeal collateral status was assessed on admission with single-phase CT-angiographies using a validated 4-point score. Patients were categorised into large-artery atherosclerosis (LAA), cardioembolic (CE), small-vessel disease (SVD) and cryptogenic (CG) according to the TOAST classification. We performed ordinal and binary (poor [collaterals filling ≤50% of the occluded territory] vs good [collaterals filling >50% of the occluded territory] collateralisation) logistic regression to evaluate the impact of TOAST aetiology on collateral status.RESULTS: Among 191 patients, LAA patients had better collateral status compared to non-LAA aetiology (LAA: 2 vs CE: 2 vs SVD: 3 vs CG: 2, pLAA vs non-LAA = 0.04). In weighted multivariate logistic regression, LAA and SVD independently predicted better collateral status (binary models [adjusted odds ratio; aOR]: LAA: 3.72 [1.21–11.44] and SVD: 4.19 [1.21–14.52]; ordinal models [adjusted common odds ratio; acOR]: LAA: 2.26 [95% CI: 1.23–4.15] and SVD: 1.94 [1.03–3.66]), while CE predicted worse collateral status (binary models [aOR]: CE: 0.17 [0.07–0.41]; ordinal models [acOR]: CE: 0.24 [0.11–0.51]).CONCLUSION: The aetiology of ischaemic stroke is associated with leptomeningeal collateral status on single-phase CT-angiography, with LAA and SVD predicting better and CE predicting worse collateral status.